2022
DOI: 10.3389/fpsyg.2022.906610
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Role of Corporate Social Responsibility for Sustainable Environmental Performance: Mediating Roles of Environmental Strategy and Environmental Outcomes

Abstract: This study examines the relationship between corporate social responsibility (CSR) and environmental performance, utilizing data from 415 small and medium-sized enterprises (SMEs) in China as a case study. We found that CSR has a direct and significant impact on environmental performance (EP) and is positively correlated to environmental strategy (ES) and environmental outcomes (EO), both of which improve environmental performance, i.e., they serve as a significant mediating factor between CSR and environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Similarly, the relationship between 'intrinsic orientation' and sustainability performance has not always shown a positive correlation (X. Wang and Bian, 2022). Considering these diverse findings of past research, this study opted to test the moderating effect of GTL by framing the hypothesis that CP and ER can perform better in the presence of green-oriented visionary leadership working at the top levels.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the relationship between 'intrinsic orientation' and sustainability performance has not always shown a positive correlation (X. Wang and Bian, 2022). Considering these diverse findings of past research, this study opted to test the moderating effect of GTL by framing the hypothesis that CP and ER can perform better in the presence of green-oriented visionary leadership working at the top levels.…”
Section: Discussionmentioning
confidence: 99%
“…Driven by a deep concern for the environment, eco-entrepreneurs are the change makers of the business world, introducing sustainable practices into manufacturing and beyond (Wang & Bian, 2022). As environmental awareness increases, companies are increasingly being required to recognize environmental protection as part of their CSR.…”
Section: Corporate Social Responsibilitymentioning
confidence: 99%
“…The financial benefits of CSR are gaining traction in academic circles, with researchers exploring how minimizing operational harm to the environment can lead to improved profitability. Recent research has revealed that companies engaged in CSR practices can more easily access capital from investors who are concerned about environmental issues(Simmou et al 2023;Waheed & Zhang, 2022;Wang & Bian, 2022). Therefore, companies can easily improve their financial performance.…”
mentioning
confidence: 99%
“…However, it is not clear whether governments in the effort to keep companies afloat and minimize unemployment have considered the companies' environmental performance before providing COVID-19 rescue packages. There is a direct and significant impact of ESG on EP (Wang and Bian, 2022). The predominant view is that companies focusing on EP signal stakeholders their long-term commitments and enhances shareholder value.…”
Section: Introductionmentioning
confidence: 99%